CRITICAL REVIEW ON THE ROLE OF NURSES IN DISASTER PREPAREDNESS AND RESPONSE IN BUILDING RESILIENCE IN HEALTHCARE SYSTEMS - Budur Hammad Alharthi, Abdulrahman Fahad Aldawsari, Jamela Muohamed Alshehri, Mohammad khalaf alanazi, Abdullah Abdulaziz Z Alsahli, Hanan Ali Hussein Hakami, Ahlam Mufleh Alrashidi, Mohammed Aziz Alharbi (Chelonian Research Foundation, 2023)
This critical review assesses the basic part of caregivers in catastrophe readiness and response, highlighting their significance in reinforcing well-being systems. Assessing current literature, strategies, discoveries, and talks about, this review gives knowledge into the part of nursing in decreasing the impacts of harm in healthcare offices. Most discoveries highlight the numerous commitments of nursing staff and their potential to make strides in healthcare execution. Furthermore, this review gives suggestions for future investigative headings and viable applications to reinforce nursing's part in injury, damage, and well-being management. Keywords: Nurses, Disaster Preparedness, Response, Healthcare Systems, Resilience